"Doing Peace": The Role of Ex-Political Prisoners in Violence Prevention Initiatives in Northern Ireland. (2nd December 2017) - Joyce, Carmel; Lynch, Orla
ABSTRACT: While a considerable amount of research has been conducted on community-based initiatives aimed at preventing violence, including the role of the ex-political prisoner community in preventative and counterterrorism work, little is known about how the ex-prisoners themselves manage their identity transition between the role they occupied during the conflict and their current role in violence prevention. We argue that it is important to consider the perspective of ex-prisoners who are both architects of their own process of desistance from political violence, as well active leaders of bespoke desistance programs. While many researchers have recognized the utility of the role of ex-prisoners in violence prevention work, theoretically, the way in which ex-prisoners do violence prevention through their use of language and intergroup contact and other resources, is poorly understood. Ultimately, the aim of the article is twofold: to understand the resources (discursive or otherwise) that the community of ex-political prisoners use in their preventative work and (2) to understand how this community understand their role in desistance programs in the context of their personal involvement in violent conflict, including the ways in which participants manage their identity transition.